The indica nitrate reductase gene OsNR2 allele enhances rice yield potential and nitrogen use efficiency - Zhenyu Gao (Nature Portfolio, 2019)
Indica rice has higher nitrate assimilation and nitrogen use efficiency (NUE) than japonica rice, but the mechanism is unclear. Here, the authors reveal that the difference is partly due to allelic variation of a nitrate reductase encoding gene and this indica allele can increase yield potential and NUE.